Elevated Cerebrospinal Fluid Tau Protein Concentrations on Admission Are Associated With Long-term Neurologic and Cognitive Impairment in Ugandan Children With Cerebral Malaria. (2nd May 2019) - Datta, Dibyadyuti; Conroy, Andrea L; Castelluccio, Peter F; Ssenkusu, John M; Park, Gregory S; Opoka, Robert O; Bangirana, Paul; Idro, Richard; Saykin, Andrew J; John, Chandy C
Abstract: Background: Elevated concentrations of cerebrospinal fluid (CSF) tau, a marker of axonal injury, have been associated with coma in severe malaria (cerebral malaria [CM]). However, it is unknown whether axonal injury is related to long-term neurologic deficits and cognitive impairment in children with CM. Methods: Admission CSF tau concentrations were measured in 145 Ugandan children with CM and compared to clinical and laboratory factors and acute and chronic neurologic and cognitive outcomes. Results: Elevated CSF tau concentrations were associated with younger age, increased disease severity (lower glucose and hemoglobin concentrations, malaria retinopathy, acute kidney injury, and prolonged coma duration, all P < .05), and an increased CSF:plasma albumin ratio, a marker of blood–brain barrier breakdown ( P < .001). Admission CSF tau concentrations were associated with the presence of neurologic deficits at hospital discharge, and at 6, 12, and 24 months postdischarge (all P ≤ .02). After adjustment for potential confounding factors, elevated log10 -transformed CSF tau concentrations correlated with worse cognitive outcome z scores over 2-year follow-up for associative memory (β coefficient, –0.31 [95% confidence interval [CI], –.53 to –.10]) in children <5 years of age, and for overall cognition (–0.69 [95% CI, –1.19 to –.21]), attention (–0.78 [95% CI, –1.34 to –.23]), and working memory (–1.0 [95% CI, –1.68 to –.31]) in children ≥5 years of age (all P < .006). Conclusions: Acute axonal injury in children with CM is associated with long-term neurologic deficits and cognitive impairment. CSF tau concentrations at the time of the CM episode may identify children at high risk of long-term neurocognitive impairment. Abstract : In children with cerebral malaria, severe disease and blood–brain barrier breakdown were associated with increased admission concentrations of cerebrospinal fluid tau, a marker of axonal injury, which were in turn associated with long-term neurologic and cognitive impairment.